A területi béregyenlőtlenségek összetevői - László Czaller; József Nemes-Nagy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– In this paper, we investigate how much of the wage differences between workers and districts is explained by employee and employer characteristics and by differences in regional characteristics. For this purpose, we use the Ministry of Finance's annual wage survey, which provides detailed data on workers' earnings, individual characteristics and the employers. Our results show that individual characteristics of workers, in particular the type of job held and educational attainment, play a leading role in explaining the wage differentials observed at the individual level. The explanatory power of employer-level characteristics is secondary, but still exceeds the combined contribution of regional characteristics, which is estimated at 1-3% at most. When examining district-level average wage differentials, we find that the composition of workers and employers in districts is responsible for three quarters of spatial wage inequalities. By removing the composition effect, the standard deviation of average gross monthly wages between districts is reduced to one third. These results underline the role of policy interventions to develop human capital in catching up disadvantaged areas.
Keywords: J24; J31; R23; 330; wage; labour markets; worker composition; wage inequalities; district